Alveolar bone trabeculae in patients with aggressive patients with aggressive periodontitis using cone beam computed tomography imaging - Shaliha, Shaliha; Firman, Ria Noerianingsih; Rusyanti, Yanti (Padjadjaran Journal of Dentistry, 2012)
Introduction: Periodontitis is an inflamatory process in supporting tissues of the teeth including the gingiva, cementum, periodontal ligament and alveolar bone. Perioditis ntitis begins with migration of junctional ephithelium toward the apical side and form a pocket on gingiva. Aggressive periodontitis is one of the classifications of periodontitis with characteristics of attacking teens to young adults in relatively fast can lead to severe alveolar bone loss and it is not comparable with local factors that there. Trabeculae are part of the alveolar bone covered by compact bone and cortical bone harder . On radiographs, trabeculae only seen as a radiolucent surrounded by a radiopaque. The purpose of this research was to know the description of alveolar trabecular bone in patients with aggressive periodontitis using Cone Beam Computed Tomography imaging. Methods: This study is descriptive on 72 samples of aggressive periodontitis alveolar travecular bon e by CBCT imaging, taken from 6 archival aggressive periodontitis patients as research subjects, obtained from secondary data in the Radiology Department of RSGM FKG UNPAD. Results: The results of this study from the 3D CBCT imaging of alveolar trabecular bone leading to further describe the more posterior a decline in trabecular bone density and decrease in patients with aggressive periodontitis. Conclusion: The 3D CBCT imaging of alveolar trabecular bone leading to further describe the more posterior a decline in trabecular bone density and decrease in patients with aggressive periodontitis.